THESAURUSES AND THEIR IMPACT ON SEMANTIC ENRICHMENT AND LANGUAGE PROFICIENCY - Najmiddinov, Muhammadjon (University Research Base, 2024)
This article explores the impact of thesauruses on semantic enrichment and language proficiency. Thesauruses are not only a tool for finding synonyms but also play a crucial role in vocabulary expansion and enhancing language understanding. This paper examines the types and functions of thesauruses, emphasizing their significance for learners, writers, and language professionals. Through a detailed analysis, the study highlights the ways in which thesauruses can aid in avoiding repetition, improving word choice precision, and fostering creativity. The article also addresses the evolution of thesauruses, from traditional print to digital formats, and their implications for language learners in the digital age.